Mid-term subclinical myocardial injury detection in patients who recovered from COVID-19 according to pulmonary lesion severity - Chamtouri, Ikram; Kaddoussi, Rania; Abroug, Hela; Abdelaaly, Mabrouk; Lassoued, Taha; Fahem, Nesrine; Cheikh'Hmad, Saoussen; Ben Abdallah, Asma; Jomaa, Walid; Ben Hamda, Khaldoun; Maatouk, Faouzi (Frontiers in Cardiovascular Medicine, 2022)
Background Severe acute respiratory syndrome coronavirus 2 (SARS-CoV 2) may cause damage of the cardiovascular system during the acute phase of infection. However, Recent studies described a mid and long-term subtle cardiac injuries after recovery from acute Coronavirus disease 19 (COVID-19). The aim of this study was to determine the relationship between the severity of chest computed tomography (CT) lesions and the persistence of subtle myocardial injuries at mid-term follow-up of patients recovered from COVID-19 infection. Methods All COVID-19 patients were enrolled prospectively in this study. Sensitive troponin T (hsTnT) and chest CT scan was performed in all patients at the acute phase of Covid-19 infection. At the mid-term follow up, conventional transthoracic echocardiograph and global longitudinal strain (GLS) of left and right ventricles (LV and RV) were determined and compared between patients with chest CT scan lesions less than 50% (Group 1) and those with severe chest CT scan greater or equal to 50% (Group 2). Results The mean age was 55 ± 14 years. Both LV GLS and RV GLS were significantly decreased in the group 2 (p=0.013 and p=0.011, respectively). LV GLS value more than -18 was noted in 43% of all the patients and RV GLS value more than -20 was observed in 48% of them. The group with severe chest CT scan lesions included more patients with reduced LV GLS and reduced RV GLS than the group with mild chest CT scan lesions (G1:29% vs. G2:57%, p=0.002) and (G1:36% vs. G2:60 %, p=0.009) respectively). Conclusion Patients with severe chest CT scan lesions are more likely to develop subclinical myocardial damage. TTE could be recommended in patients recovering from COVID-19 to detect subtle LV and RV lesions.